Case Study of Student Learning Difficulties in Mathematics Learning at MTs Muallimin Univa Medan - Simamora, Minta Ito; Wati, Sartika; ‘Aini, Fadhlul; Rodiah, Rodiah (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study aims to describe the types of mathematics learning difficulties experienced by students at MTs Muallimin Univa Medan and the contributing factors. The research method used is descriptive qualitative. The research subjects consisted of 7th- grade students and mathematics teachers. Data collection was conducted through classroom observations, in-depth interviews, and diagnostic test analysis. The results showed that the students’ main difficulties included difficulty in understanding abstract concepts, weaknesses in basic arithmetic operations, and low contextual problem-solving abilities. The factors causing these difficulties stem from internal factors (low motivation and math anxiety) and external factors (less varied teaching methods and lack of learning support at home).